2017
DOI: 10.1038/srep41714
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prevalence and Factors Associated with Nocturia in Adult Korean Men

Abstract: This study investigated the prevalence of and factors associated with nocturia in Korean men. A total of 92,626 participants aged between 19 and 103 years from the 2011 Korean Community Health Survey (KCHS) were enrolled. Simple and multiple logistic regression analyses with complex sampling investigated participants’ personal health and socioeconomic and disease factors. The prevalence of nocturia ≥1 time and ≥2 times/night was 41.8% and 17.6%, respectively, and nocturia increased with age (1.44 [1.39–1.50] f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
3
14
0
1
Order By: Relevance
“…In addition, the prevalence of nocturia was found to increase with age, which corroborated the ndings of other studies [4,5,18]. This may be due to various pathophysiological mechanisms that related to ageing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the prevalence of nocturia was found to increase with age, which corroborated the ndings of other studies [4,5,18]. This may be due to various pathophysiological mechanisms that related to ageing.…”
Section: Discussionsupporting
confidence: 90%
“…Nocturia is strongly associated with various risk factors and comorbidities, including cardiovascular diseases, diabetes, sleep disorders, somatic and mental health [6,13,18,22,23]. This supports the ndings of this study which also showed the signi cant higher disease prevalence among respondents with comorbidities such as hypertension, diabetes mellitus, renal disease or overactive bladder.…”
Section: Discussionsupporting
confidence: 87%
“…Continuous variables were assessed using a t-test, whereas categorical variables were assessed using Pearson chi-square test. Because several studies have reported that the prevalence of nocturia differs according to age, sex, obesity, and underlying diseases such as hypertension, DM, and dyslipidemia, 8,10) we performed a multivariate logistic regression analysis with these variables to determine the odds ratios (ORs) for nocturia. In addition, we conducted a subgroup analysis based on sex and underlying diseases.…”
Section: Structural Analysismentioning
confidence: 99%
“…[6][7][8] According to the Korean Community Health Survey, the prevalence of nocturia has rapidly increased with aging. 8) More specifically, nocturia results in reduced quality of life and work productivity in older adults. [8][9][10][11][12][13][14] Nocturia also increases the risk of falls and fractures by increasing the frequency of waking up to urinate during the night, which eventually results in an increased mortality rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation